Memory, tradition, and text : uses of the past in early Christianity - Kirk, Alan (Alan K.); Thatcher, Tom, 1967- (Atlanta, USA, SBL Press, 2005)
Social and cultural memory theory examines the ways communities and individuals reconstruct and commemorate their pasts in light of shared experiences and current social realities. Drawing on the methods of this emerging field, this volume both introduces memory theory to biblical scholars and restores the category "memory" to a preeminent position in research on Christian origins. In the process, the volume challenges current approaches to research problems in Christian origins, such as the history of the Gospel traditions, the birth of early Christian literature, ritual and ethics, and the historical Jesus. The essays, taken in aggregate, outline a comprehensive research agenda for examining the beginnings of Christianity and its literature and also propose a fundamentally revised model for the phenomenology of early Christian oral tradition, assess the impact of memory theory upon historical Jesus research, establish connections between memory dynamics and the appearance of written Gospels, and assess the relationship of early Christian commemorative activities with the cultural memory of ancient Judaism. --From publisher's description
Social and cultural memory / Alan Kirk -- Jesus tradition as social memory / Alan Kirk and Tom Thatcher -- Christian origins : historical truth and social memory / Barry Schwartz -- Prominent patterns in the social memory of Jesus and friends / Richard A. Horsley -- Why John wrote a gospel : memory and history in an early Christian community / Tom Thatcher -- The story of "the woman who anointed Jesus" as social memory : a methodological proposal for the study of tradition as memory / Holly Hearon -- The locus for death : social memory and the Passion Narratives / Arthur J. Dewey -- Christian collective memory and Paul's knowledge of Jesus / Georgia Masters Keightley -- Collective memory and Hebrews 11 : outlining a new investigative framework / Philip F. Esler -- Early Jewish birth prophecy stories and women's social memory / Antoinette Clark Wire -- The memory of violence and the death of Jesus in Q / Alan Kirk -- Reading the Gospel of Thomas as a repository of early Christian communal memory / April D. DeConick -- The works of memory : Christian origins as mnemohistory -- a response / Werner H. Kelber -- Jesus in first-century memory -- a response / Barry Schwartz
Includes bibliographical references (pages 263-279)
Keywords: Bible -- Criticism, interpretation, etc; Church history -- Primitive and early church, ca. 30-600; History -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600; Memory -- Religious aspects -- Christianity -- History of doctrines -- Early church, ca. 30-600